" Столетья не сотрут...": русские классики и их читатели / сост. А. А. Ильин -Томич - Ильин -Томич А. А. (Судьбы книг, 1989)
Экземпляры: абонемент (20150811) / Инвентарный номер: 25033 / Цена: 1.90 / Авт.знак: С 81 / ГРНТИ: 17 / ББК: 83.3(2Рос=Рус)1